Solar Cells: Spanning the Solar Spectrum: Azopolymer Solar Thermal Fuels for Simultaneous UV and Visible Light Storage (Adv. Energy Mater. 3/2017). Issue 3 (February 2017) - Saydjari, Andrew K.; Weis, Philipp; Wu, Si
Abstract : Implementation of azobenzene‐based solar thermal fuels remains challenging because UV light, a small fraction of the solar spectrum, is required for charging. In article number 1601622, Si Wu and co‐workers report a four‐layer solar thermal cell that stores both UV and visible light from the sun. This cell achieves a record solar efficiency (0.4%) amongst azobenzene‐based solar thermal fuels.